Characteristics Early versus Late Recurrent Ischemic Stroke: A Scoping Review on Timing and Predictors - Christina, Mikha; Eli Kosasih, Cecep; Prawesti, Ayu (Journal of Health and Nutrition Research, 2025)
Recurrent ischemic stroke (RIS) is a major global health issue due to its high morbidity, mortality, and economic burden. While numerous studies have explored the timing and pattern of RIS globally, there is a limited understanding of this issue within the Indonesian context. In the absence of sufficient local data, synthesizing global evidence becomes crucial to inform clinical practice and policy development in regions like Indonesia. This review aimed to explore timing patterns of RIS especially early and late phases and estimate risks based on follow-up, to inform evidence-based interventions. A scoping review based on Arksey & O’Malley framework and PRISMA-ScR guidelines. Literature search (2014–2024) in PubMed, Scopus, ScienceDirect, and CINAHL. Nine studies were included and analyzed thematically. From 2,987 articles, 9 met inclusion criteria. RIS risk ranged 4.3–23.4%, with median recurrence time 21–25 days. Early RIS (<90 days) had distinct risk factors (e.g. hypertension, prior stroke, heart disease) compared to late RIS. Modified Rankin Scale (mRS) and National Institutes of Health Stroke Scale (NIHSS) were key instruments; follow-ups done via clinics, registries, or surveys. Early (<90 days) and late recurrent ischemic strokes differ in both risk factors and clinical implications. Early post-stroke monitoring is critical to reducing recurrence. To address long-term prevention and support adherence to secondary prevention strategies, technology-assisted monitoring or broader digital health solutions should be considered as potential interventions, particularly in overcoming challenges related to long-term follow-up and patient engagement.